2021
DOI: 10.3390/healthcare9111417
|View full text |Cite
|
Sign up to set email alerts
|

Organic Collaborative Research Partnership Building: Researchers, Needle and Syringe Program Providers, and People Who Inject Drugs

Abstract: (1) Background: People who inject drugs (PWID) and needle and syringe program (NSP) providers increasingly partner with researchers to explore harm reduction best practice. However, a paucity of research exists regarding how best to engage PWID and community NSP providers to generate the evidence for sustainable harm reduction services. (2) Aim: This study reports on our use of an organic community research partnership-building approach between researchers, NSP providers, and PWID in Canberra ACT, Australia. (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The cardiology clinicians collaborated on earlier physical activity trials 41,47 and feasibility studies of the MindMoves intervention 49,63 and were essential in developing inclusion criteria and study protocols that informed recruitment and screening. Our clinician-researcher partnerships were fostered on mutual trust and the goal of improved health of the clinic patients, which are known to be important predictors of successful collaboration between clinicians and researchers 73,74 . Yet, we found that engaging all clinic clinicians was challenging, so we relied on a few clinician champions for patient referrals.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The cardiology clinicians collaborated on earlier physical activity trials 41,47 and feasibility studies of the MindMoves intervention 49,63 and were essential in developing inclusion criteria and study protocols that informed recruitment and screening. Our clinician-researcher partnerships were fostered on mutual trust and the goal of improved health of the clinic patients, which are known to be important predictors of successful collaboration between clinicians and researchers 73,74 . Yet, we found that engaging all clinic clinicians was challenging, so we relied on a few clinician champions for patient referrals.…”
Section: Discussionmentioning
confidence: 98%
“…Our clinician-researcher partnerships were fostered on mutual trust and the goal of improved health of the clinic patients, which are known to be important predictors of successful collaboration between clinicians and researchers. 73,74 Yet, we found that engaging all clinic clinicians was challenging, so we relied on a few clinician champions for patient referrals. In an earlier study that used clinician referrals for recruitment to a parent training behavioral trial, clinicians and clinic staff also noted some major barriers to referrals.…”
Section: Discussionmentioning
confidence: 99%